Global determinants of stress and risk in public-private partnerships (PPP) in infrastructure - Renato E. Reside (Asian Development Bank Institute (ADBI), 2009)
This study analyzes the determinants of stress in public-private partnerships (PPPs) in infrastructure investment. While project failures seldom occur, there are many stresses that hinder success. One of these is broad political risk: the prerogative of government executives to make sweeping changes in investment rules or regulations - through measures such as protracted tariff freezing - that undermine a project's market value. Broad political risk can constitute the biggest threat to project outcomes. However, this is usually only realized after other risks, such as currency risk, have materialized first. Thus, broad political risk can be controlled. The empirical analysis in this study yields a number of surprising results: (i) strong growth and rigid currency regimes heighten risk by leading to adverse selection of proponents and moral hazard in project design; (ii) many of the World Bank's indices of governance quality lead to perverse outcomes, suggesting that new governance standards must be used to judge PPPs; and (iii) except for political risk guarantees, loans and equity from multilateral institutions have no effect on outcomes; however, political risk guarantees are rarely utilized, suggesting that they may need to be redesigned or marketed better to be more useful. The paper concludes with suggestions for policy improvements.
Keywords: H54; H81; F21; 330